Antioxidant status and clinicopathological parameters in patients with Parkinson's disease - Miletić Vukajlović, Jadranka; Pejić, Snežana; Todorović, Ana; Valenta Šobot, Ana; Drakulić, Dunja; Pavlović, Ivan; Stefanović, Aleksandra; Prostran, Milica; Ilić, Tihomir V; Stojanov, Marina (Vojnosanitetski pregled, 2021)
Backgroun/Aim. Constant production of free radicals and antioxidants (AO) in cells is a part of normal cellular function. Their imbalance might take a part in pathophysiology of many diseases, including Parkinson’s disease (PD). Evaluation of the disease status, prooxidant-antioxidant balance (PAB) and antioxidants are being widely estimated. The aim of this study was to examine potential interaction between several AO variables: glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and PAB, and clinicopathologic features of patients with PD, particularly the Hoehn and Yahr (H&Y) stage. Methods. A multivariate analysis of variance (MANOVA) was conducted to analyze mean differences between clinicopathologic characteristics (gender, age at examination, duration of the disease, and the H&Y stage) and AO variables of PD patients and those of age/sex matched healthy controls. The study included 91 patients with idiopatic PD patients and 20 healthy persons. Results. The multivariate effect size was estimated at 0.269 (p
Keywords: parkinson disease; disease progression; free radicals; antioxidants; demography